Ferramenta tecnológica de gestão orçamentária em uma unidade universitária - Manica, Daniel (2024)
The public budget is the means by which various government institutions can carry out practically all their activities and public higher education institutions are no different, as they depend on this resource to maintain their entire chain of services. In this sense, the Federal University of Santa Maria, aiming at teaching, research and extension, has its Teaching Units as the main application of its resources and therefore it is necessary to make use of instruments that allow these funds to be managed efficiently. Thus, the present study sought to understand how this budget management takes place in a Teaching Unit at UFSM in order to identify needs and functionalities of a technological information and communication tool that can make the management of resources in this unit more effective. A descriptive research was used, with a qualitative approach that uses an agile systems development methodology to build this tool. Therefore, the research was carried out through semi-structured interviews with potential users of this technology, which identified inefficient budget management, which requires greater planning, control, updating and communication between sectors. Thus, the research sought to understand these difficulties, concerns and best practices in relation to budgeting and to develop and evaluate a tool that promotes budgetary effectiveness and thus identify the necessary requirements to serve users. Based on the information and cooperation of a software programmer, the first modules of the tool were developed, in addition to testing with some key users that brought greater refinement to the system after its first version. The next steps will involve improving the system and effective implementation and use.